The State, the Market, and Higher Education. Challenges for the New Century - Kwiek, Marek (My University, 2003)
The university in its modern form (invented 200 years ago by German Idealists and Romantics for the University of Berlin) has traditionally been in very close relations with the state and in relatively distant relations with the market. Now, as state/ market relations are changing with the advent of globalization, the university is unexpectedly located in a different landscape in which the state is generally - with notable exceptions - becoming weaker, and the market is becoming stronger. The university, traditionally a very important part of the public sector, is coming under public scrutiny and its social and cultural missions are being increasingly challenged. In the last half a century, despite immense growth in enrollments, and moving towards massification and near-universalization, public higher education remained relatively stable from a qualitative point of view and its fundamental structure remained unchanged. No major changes occurred that were as revolutionary as the changes we are currently witnessing. What we are seeing today is the very beginning of these transformations, though. The forces of change worldwide are similar and they are pushing higher education systems into more market-oriented and more competitive arenas (and certainly towards less state regulation). For centuries, "the market" had no major influence on higher education. Most universities in the world were created by the state and were subsidized by the state. Most students attended public institutions and most faculties worked in public institutions. Today market forces are invading higher education worldwide: while the form and pace of change is different in different parts of the world, this change is happening everywhere.
Keywords: state; market; market forces; the university and the state; globalization; higher education; universities; marketization; privatization; educational policy